Phenotypic variability of yield components in wheat grown on different soil types - Petrović Sofija; Dimitrijević Miodrag; Belić Milivoj (Selekcija i Semenarstvo, 2006)
The vast share of agricultural soil in Vojvodina province is quality chernozemic soil. However, there is still a share of halomorphic soil, solonetz type, that are not convenient for agricultural production. Phenotypic variability and correlation of spike parameters in wheat varieties derived in Novi Sad are given in this article. Wheat genotypes were sown on chernozemic soil, as well as, on solonetz soil (control and two levels of melioration 25 and 50t/ha phosphor-gypsum). The goal was to investigate varietal differences in reaction to melioration and soil type. The results obtained reveal the highest mean values of examined yield components on chernozem, as well as, different genotype reaction to meliorative measures on solonetz type of soil.